Polypropeenin fysikaalisten ominaisuuksien muutokset ekstruusioprosessissa - Parvela, Ossi (2013)
Changes in mechanical properties and reasons for twisting behaviour of thermoformed polypropylene lids is studied. The study is based on the investigation of changes in molecular weight distribution and crystallinity of isotactic polypropylene during extrusion process with different process parameters. Also the effect of additives and re-grinded material is studied. Gel permeation chromatography (GPC) was used in measurements of molecular weight distributions and crystallinities of polypropylene was measured with differential scanning calorimetry (DSC). Process parameters don't have any effect on mechanical properties of the lids but twisting behaviour diminish considerably by changing the temperature of the middle cooling calander.